Mechanical, Thermal, and Morphological Properties of Recycled PP and HDPE Green Composites Reinforced with Atriplex halimus Fibers - Amira Aberkane; Hayet Bendaikha; Rachid Benzidane; Jean-Baptiste Jouenne; Ibrahim M. H. Alshaikh; Ahmed Belaadi; Djamel Ghernaout (Journal of Natural Fibers)
This study investigates the use of natural fibers extracted from Atriplex halimus as reinforcement in recycled thermoplastic composites. Initially, the characterization of both treated and untreated fibers was conducted to determine their chemical composition, morphological features, and tensile behavior. The study then focused on using untreated fibers, which were incorporated at different loading rates (5, 10, and 15 wt%) into matrices of recycled polypropylene (rPP) and recycled high-density polyethylene (rHDPE) by compression molding. Mechanical characterization of the composites made with untreated fibers indicated that the strength retention of rPP composites (87.1% at 15% loading) was better than that of rHDPE composites, but the stiffness improvement of rHDPE composites was higher (59.4% increase at 15% loading). The optimal untreated fiber content was 5 wt%, at which rPP composites exhibited 96.8% strength retention and 41.8% modulus improvement, whereas rHDPE composites displayed 97.3% strength retention and 23.2% modulus enhancement. At a loading of 5%, better fiber-matrix adhesion in rPP composites was confirmed via SEM analysis. These results, achieved with untreated A. halimus fibers, promote their use as an attractive reinforcement option in sustainable applications for maximizing their potential in recycled thermoplastics.